Plexiform Schwannoma of the Tongue in a Pediatric Patient with Neurofibromatosis Type 2: A Case Report and Review of Literature - Samir M. Amer; Aijan Ukudeyeva; Harold S. Pine; Gerald A. Campbell; Cecilia G. Clement (Hindawi Limited, 2018)
Introduction. Plexiform schwannoma is a rare variant of schwannoma that accounts for only 5% of all schwannomas. Herein, we present a rare case of plexiform schwannoma of the tongue in a pediatric patient with neurofibromatosis type 2 (NF2). Case Presentation. A 13-year-old female presented with a growing left-sided tongue mass. The patient has a past medical history of NF2. The tongue mass was excised and histopathological examination revealed a spindle cell tumor with multinodular growth pattern, with Verocay bodies' formation. Tumor cells were strongly positive for S-100 protein and negative for smooth muscle actin (SMA), and EMA highlighted perineural fibroblasts surrounding tumor nodules. These findings were diagnostic of plexiform schwannoma. Conclusion. Plexiform schwannoma of the tongue is an extremely rare tumor seen in patients with NF2. Clinical examination and histopathological evaluation are important for diagnosis of plexiform schwannoma.